Experimental development of stiffness-variable foot sole mechanism for bipedal robots - Ahmad Najmuddin, Ibrahim (2013)
This research aims to develop a novel foot sole mechanism which utilizes the jamming transition effect of granular material enclosed in an air tight bag, for use by bipedal robot walking on uneven ground. Zero Moment Point control based robots depends heavily on the accuracy of the modeling of the walking environment, making it weak towards outer disturbances such as uneven walking grounds. The purpose for the development of the foot sole mechanism is to increase the robustness of the Zero Moment Point control based bipedal robots against uneven ground surface irregularities. The mechanism is designed to make the foot sole be soft and compliant to adapt to the surface of an uneven terrain, and be stiff when the robot is in the support phase of the walking gait. Stiffness-variable property of the mechanism according to the internal air pressure of the bag is investigated. The stiffness that could be achieved by the proposed stiffness-variable mechanism is concluded to be enough to support a 60[kg] robot. To measure the effectiveness of the proposed mechanism when placed on an uneven ground, an experiment using a single robot leg to simulate the change in Zero Moment Point when a bipedal robot is in a single leg support gait cycle had been performed. From the measured ZMP position trajectory, when the proposed foot sole mechanism is used, the robot is able to maintain the same ZMP trajectory as when the robot is moving on a flat ground using a rigid sole, even when obstacles is randomly placed under the foot sole. It is concluded that the proposed stiffness-variable foot sole mechanism allows better ZMP measurement and control on uneven ground.